Thermal convection of magneto compressible couple-stress fluid saturated in a porous medium with hall current - Mehta, C.B.; Singh, M.; Kumar, S. (Zielona Góra: Uniwersytet Zielonogórski)
An investigation is made on the effect of Hall currents on thermal instability of a compressible couple-stress fluid in the presence of a horizontal magnetic field saturated in a porous medium. The analysis is carried out within the framework of the linear stability theory and normal mode technique. A dispersion relation governing the effects of viscoelasticity, Hall currents, compressibility, magnetic field and porous medium is derived.
Keywords: couple-stress fluid; horizontal magnetic field; compressibility; porous medium; Hall currents